STRATEGI KOMUNIKASI PEMASARAN TERPADU EKOWISATA DI KEBUN RAYA EKA KARYA, BEDUGUL, BALI - Muntadliroh, Muntadliroh (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016DO - 10.24843/JUMPA.2016.v03.i01.p04)
Ecotourism of Bali Botanical Garden, Bedugul, Tabanana Regency, Bali, has been able to increase the number of visitors from time to time though it is still far from the optimum level. In 2010-2011 the number of visitors at Bali Botanical Gardens was counted for 368.927 people. Based on the data, visitors interest to visit Bali Botanical Garden are still low. Facing this problem, integrated marketing communication strategy is needed.This paper discusses implementation of integrated marketing communication concept created by Philip Kotler to the market ecotourism at Bali Botanical Garden, by using case study for qualitative research.The results of this analysis show that implementing this concept made a better relationship between Bali Botanical Garden and its visitors, also increasing quantity of its visitors.
Keywords: Bali Botanical Garden, Ecotourism, Integrated Marketing Communications